Blue-eyed een erefer blue-eyed women: the role of life history strategies and sociosexuality : individual differences in eye colour preferences - Gračanin, Asmir (Array, 2021)
Previous research (Laeng et al., 2007) conducted on Norwegian samples showed that blue-eyed men rate blue-eyed women as more attractive, while brown-eyed men and all the women show no differences in attractiveness assessments with respect to eye colour. Correspondingly, positive assortative mating was found for blue, but not brown eyes, and it most often occurred in blue-eyed men. We aimed to replicate this blue-like-blue effect in the Croatian population, which differs in the ratio of eye colour phenotypes (blue eye colour is the most prevalent in Norway while brown is the most prevalent in Croatia). Additionally, we examined whether this effect is moderated by life history strategies and sociosexuality. Our hypothesis was that the effect would be larger in those blue-eyed men who exert a slower life history strategy and who are sociosexually restrictive. One hundred and twenty-eight participants assessed the attractiveness of blue-eyed and brown-eyed models, whose eye colours were experimentally manipulated in such a way that participants were shown models with natural or artificially changed eye colours. The blue-like-blue effect was replicated in the context of preferences, although it was smaller than in the original study. However, unlike the original study, in a sample of 138 participants no assortative pairing by eye colour was found between participants and their romantic partners. Finally, the hypothesis about the moderation was supported for life history strategies, but not for sociosexuality. In addition to the rationale for the blue-like-blue effect based on the paternity uncertainty account, which was offered by the authors of the original study, we discussed other accounts of this phenomenon.